THE ERA OF TRANSPARENCY: AUDITOR’S JUDGEMENT OF KEY AUDIT MATTER AND AUDIT QUALITY (Journal of Business Management and Accounting, 2024)
This paper discusses the theoretical influence of key audit matter and audit quality. This paper discusses a literature study method approach to explore the possible impact of key audit matters (KAMs) and audit quality. In particular, the authors believe implementing key audit matters can largely affect audit risk, going concern evaluation and audit response procedures, which in the end can influence on audit quality. Implementation of key audit matters in Indonesia began in 2022, audit firms are strongly advised to prepare better audit working papers and mitigate audit risks. This can help them consider matters that require the auditor's significant attention, which in turn is hoped can increase the flexibility and effectiveness of communication between auditees and auditors. In addition, the author recommends that regulators or audit oversight boards require the application of boards to apply key audit matters to all audit work, not just mandatory for listed companies. It is hoped that this rule will help audit companies work more carefully in dealing with audit risks, which appear to be positively related to audit quality. As far as the author knows, limited educational study has explored the possible influence of key audit matters (KAMs) on audit quality in Indonesia. Therefore, this paper reduces the research gap in the audit literature. On the other hand, this paper can be used as a foundation for developing research instruments (e.g., questionnaires, interviews, or content analysis) to grant empirical evidence.